MATHEMATICAL LITERACY: A BIBLIOMETRIC MAPPING OF THE RESEARCH LITERATURE IN INDONESIA IN THE LAST DECADE (2014 – 2024) - Simbolon , Asep; Nurjanah (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Mathematical literacy is one of the main focuses of Indonesian education. There are many research literatures on mathematical literacy so it is important to do a bibliometric mapping. The purpose of this study is to comprehensively describe and visualize research trends on mathematical literacy in mathematics learning in the last decade in Indonesia. The sample of this study was 139 research publications obtained from the Scopus database using the keyword "mathematical literacy", “Numeracy” and “PISA”. This research method uses bibliometric analysis assisted by VOS Viewer software. The results showed that the highest number of publications of mathematical literacy research in the last ten years was in 2023. Journal on Mathematics Education, Sriwijaya University is the affiliation that publishes the most publication documents related to mathematical literacy. Research topics that have not appeared based on keywords such as computational thinking, spatial ability, adversity quotient, self-regulated, and virtual reality can be used in future research for a wider research area.